LANGUAGE AS A SIGN OF THE NATION AND SYMBOL OF THE STATE - Головачева, К.Р. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The article deals with the interconnection of formation of Ukrainian language as the state language and its role in shaping the political nation in Ukraine. It is proved that language policy can be an effective rallying point only if it reflects the diversity of language spectrum and have a clear regulatory legislative acts and solving existing problems, the problem of choosing the state language is most characteristic for countries that gained independence. Requirements of language policy is to define the scope of its distribution.